TRACING THE SPACE OF SASAK WOMEN: PHENOMENOLOGY OF THE PRESENCE AND SURVIVAL OF THE NENSEK TRADITION - Liza Hani Saroya Wardi; Muhammad Fadjri (International Journal of Social Science, 2026)
This paper aims to trace and understand the traces of the spatial experience of Sasak women in the nensek tradition in the hamlet of Keloke Aik Atas, Batujai Village, Praya Barat District, Central Lombok Regency. Through a phenomenological approach, it is hoped that it will be able to answer questions about (1). What is the form and meaning of the traces of the presence of Sasak women's space in the nensek tradition, (2). How is the process of the formation of Sasak women's space in the nensek tradition, (3). What factors influence the survival of Sasak women's space in the nensek tradition until now, and (4). How is the phenomenological experience of Sasak women tracing, experiencing and interpreting women's space in the nensek tradition. Data to explain this was obtained through field observations and interviews. The findings obtained from the traces of the presence of Sasak women's space in the nensek tradition are not only a weaving space but also a meeting space for them with their ancestors in the past so that Sasak women become cultural heirs in the nensek tradition inherited from their own ancestors. In addition, the presence of women's space is due to the nensek tradition itself as the "pengadek-ngadek" of ancestors whose existence must be maintained so that women's space in the nensek tradition becomes a cultural mandate for Sasak women in Keloke Aik Atas. Women's space in the nensek tradition that is formed can be seen in public zones both inside and outside the residence by following the direction of the residence facing West and East on a micro, meso and macro scale. Meanwhile, the main factor that causes the Sasak women's space in the nensek tradition to survive is the existence of high-value sesekan cloth which serves as a medium for connecting the energy of their ancestors in the past, resulting in them continuing to feel connected by carrying out the nensek tradition. The religious values contained in the nensek tradition will oversee the growth and survival of Sasak women's space in the nensek tradition. The most important thing for them is the women's space in the nensek tradition as their spiritual expression towards God, namely Allah Ta'ala. They believe that nensek activities are a means of their worship to Allah Ta'ala. These findings show that Sasak women are able to appreciate the women's space in the nensek tradition as a space for self-existence as well as a mirror of themselves so that they can see a picture of their lives both in the past, present and future so that the Sasak women's space in the nensek tradition is not only a physical space but a living space and is animated by the experiences of the space's inhabitants themselves.